Cloning the bacterial bphC gene into Nicotiana tabacum to improve the efficiency of PCB phytoremediation - Novakova, M; Mackova, M; Chrastilova, Z; Viktorova, J; Szekeres, M; Demnerova, K; Macek, T (Biotechnology and bioengineering, 2009)
The aim of this work is to increase the efficiency of the biodegradation of polychlorinated biphenyls (PCBs) by the introduction of bacterial genes into the plant genome. For this purpose, we selected the bphC gene encoding 2,3-dihydroxybiphenyl-1,2-dioxygenase from Pseudomonas testosteroni B-356 to be cloned into tobacco plants. The dihydroxybiphenyldioxygenase enzyme is the third enzyme in the biphenyl degradation pathway, and its unique function is the cleavage of biphenyl. Three different constructs were designed and prepared in E. coli: the bphC gene being fused with the beta-glucuronidase (GUS) gene, with the luciferase (LUC) gene, and with histidine tail in three separate plant cloning vectors. The GUS and LUC genes were chosen because they can be used as markers for the easy detection of transgenic plants, while histidine tail better enables the isolation of protein expressed in plant tissue. The prepared vectors were then introduced into cells of Agrobacterium tumefaciens. The transient expression of the prepared genes was first studied in cells of Nicotiana tabacum. Once this ability had been established, model tobacco plants were transformed by agrobacterial infection with the bphC/GUS, bphC/LUC, and bphC/His genes. The transformed regenerants were selected on media using a selective antibiotic, and the presence of transgenes and mRNA was determined by PCR and RT-PCR. The expression of the fused proteins BphC/GUS and BphC/LUC was confirmed histochemically by analysis of the expression of their detection markers. Western blot analysis was performed to detect the presence of the BphC/His protein immunochemically using a mouse anti-His antibody. Growth and viability of transgenic plants in the presence of PCBs was compared with control plants.
Keywords: Luciferases; exprese genu; Gene Expression; Recombinant Fusion Proteins; Biodegradation, Environmental; polychlorované bifenyly; Bacterial Proteins; dioxygenasy; Glucuronidase; Cloning, Molecular; luciferasy; reportérové geny; klonování DNA; Comamonas testosteroni; Genetic Vectors; Polychlorinated Biphenyls; rekombinantní fúzní proteiny; Agrobacterium tumefaciens; Dioxygenases; Plants, Genetically Modified; Nicotiana; glukuronidasa; bakteriální proteiny; genetické vektory; geneticky modifikované rostliny; Genes, Reporter; tabák; biodegradace